„Iron Monsters” at Piotrkowska Street. Introduction to the History of Łódź the 1st Tank Regiment on the Basis of Local Press and Selected Archives - Walkiewicz, Tomasz (Tools of War, 2023)
The 1st Tank Regiment was the very first military unit in the whole history of the Polish army, which was full fitted out with tanks. Created on March 15, 1919 by order of the Command of the Polish Army in France, it went to the independent Poland in June of the same year. Equipped with 120 modern tanks, the Renault FT took an active part in the war with Bolshevik Russia. A little-known card in his history are relations with Łódź, where he was stationed for the first two years. Łódź was the place from the fighting vehicles went to the fronts of the war, here they also went from the battlefields for renovation. In Łódź, armoured soldiers quartered, continued their military training and participated in language courses. Some aspects of the regiment’s relationship with the city were reflected in the local press of the time: „Straż Polska”, „Kurier Łódzki”, „Głos Polski”, „Rozwój”, „Praca”. News, some small ads and press announcements supplemented with individual archives from the resources of the State Archive in Łódź such as iconography, files and ephemeral prints allowed to broaden knowledge about some important aspects connected with: the reviews of tanks organized for the local population, among whom they aroused great interest; participation of the regiment in parades accompanying state and military ceremonies or church devotions; minor incidents and accidents in the city involving soldiers and drivers; a volunteer enlistment to the unit conducted among the inhabitants of Łódź in the summer of 1920 and the ceremony of decoration of officers and privates from the 1st Tank Regiment Kris Virtuti Militari in June 1921.